A rare case of left ventricular thrombus with ischemic MCA stroke in a lady with Crohn’s disease - Mandal, Manamita; Vasudev S Parashar,; Praveen Kumar Yadav,; Misra, Amar Kumar; Mukherjee, Joydeep; Mohanty, Bijendra; Kumar, Sanjay (Asian Journal of Medical Sciences, 2023)
We report a case of Crohn’s disease (CD) presenting as a thromboembolic middle cerebral artery stroke due to a left ventricular (LV) thrombus in a 50-year-old lady. The proinflammatory and procoagulant state reported in CD seems responsible for this. The patient was managed with conservative treatment, but she died quickly. The findings highlight the rare occurrence of LV thrombus in a patient of CD as well as the need for aggressive control of disease activity with disease-modifying drugs at an earlier phase of treatment.